Using the Autobiography of Intercultural Encounters as a Framework to Write Narratives of Intercultural Experiences - Defne Erdem Mete (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
This paper presents the findings of a case study that is based on the Autobiography of Intercultural Encounters AIE Byram et al., 2009 published by the Council of Europe. The council published this document as a complementary tool that can help students reflect critically on specific intercultural encounters they had. The paper argues that the document can be used not only in its original question-answer format to critically analyze intercultural experiences, but also as a framework that would help students write narratives of their intercultural encounters. Therefore, intercultural experiences of students, such as study-abroad, can be written as reflective narratives by using this document. In this study, a Turkish student who returned from an Erasmus exchange program was asked to write a narrative of one of her intercultural encounters. Then, the student wrote her answers to the questions in AIE about the same experience. By using AIE as a framework, she reviewed her first narrative and wrote its final version by adding more details that she thought would be appropriate. Content analysis of the two narratives and the student’s AIE revealed that the final version of the narrative that was written based on AIE was more critical in its perspective and detailed than the first narrative. The interview that was conducted to find out the student’s opinions of this writing experience also showed that the student found writing a narrative based on AIE beneficial both for herself and the readers. The study suggests that using AIE as a framework to write narratives of intercultural encounters would be especially useful for English language learners who use English as a lingua franca in intercultural communication situations. By reading such collected narratives, students can increase their awareness about intercultural conflict situations and develop their intercultural communicative competence